Cytokine expression and Mycoplasma hyopneumoniae burden in the development of lung lesions in experimentally inoculated pigs - Almeida, Henrique M.S. [UNESP]; Mechler-Dreibi, Marina L. [UNESP]; Sonálio, Karina [UNESP]; Ferraz, Maria Eugênia S. [UNESP]; Storino, Gabriel Y. [UNESP]; Barbosa, Fernanda O. [UNESP]; Maes, Dominiek; Montassier, Hélio J. [UNESP]; de Oliveira, Luis G. [UNESP] (Elsevier, 2020)
This study aimed to assess immunopathological factors and M. hyopneumoniae (M. hyo) load in macroscopic lesion formation at four timepoints after experimental infection of swine. To do this, 24 M. hyo-free pigs were divided into two groups: non-inoculated control (n = 8) and inoculated (n = 16). At day 0 post-infection (dpi), animals of infected group were intratracheally inoculated with 5 mL of lung inoculum containing 107 CCU (Color Changing Units) ∕mL of M. hyo strain 232, while control group was mock infected with 5 mL of sterilized Friis medium. At 14, 28, 42 and 56 dpi, four animals from the infected group and two from the control group were euthanized and necropsied. The extent of macroscopic lung lobe lesions was visually assessed, scored and lesion samples (qPCR, histopathology and gene expression) were collected. The macroscopic lesion score and estimated M. hyo load (in copies/μL) at the different timepoints were: 14 dpi: 18.5 %–1.55 × 103 copies∕μL; 28dpi: 15.8 %–8.4 × 103 copies∕μL; 42 dpi: 7.0 %–3.2 × 104 copies∕μL and 56 dpi: 6.3 %–1.11 × 105 copies∕μL; Significant and positive correlations between macroscopic lung lesion and the pathogen load were found (coefficient range: 0.77−0.99). The cytokine's IL-6 (0.73) and INF-γ (−0.69) gene expression were significantly (p < 0.05) correlated to macroscopic lung lesion score while IL-8, TNF- α, IL-1α and IL-1β were associated to other pathological effects such as losses in average daily weight gain and microscopic lesion score. The results provide a better understanding about the pathogenicity of M. hyo strain 232 and the host-pathogen interactions, which may be helpful for the development of new treatments or control measures.
Keywords: Cytokines; Gene expression; Immunology; Mycoplasma hyopneumoniae; Pork production; Swine respiratory disease